The Autism Spectrum Disorder Evaluative Education Model: a school-based method of assessing and selecting interventions for classroom use - Costley, Debra; Clark, Trevor; Bruck, Susan (SAGE, 2014)
Evaluating educational programs and interventions is generally considered a normal part of curriculum development and improvement, and published findings are readily accessible through peer-reviewed journals. Recently, however, researchers and practicing educators have identified a lack of evaluative research regarding Autism Spectrum Disorder (ASD) educational practices in the peer-reviewed literature. Autism Spectrum Australia (Aspect) has an established evidence-informed ASD curriculum that is constantly reviewed and updated to meet the needs of the students in Aspect schools and classes. Through a methodical evaluative process, all educational interventions and support processes and devices undergo a series of Evidence-Based Research Trials and evaluations before they are implemented in classes. This article demonstrates how a workflow model can deliver a systematic method for identifying, evaluating, implementing, and disseminating the research findings of a program or support intervention. The Autism Spectrum Disorder Evaluative Education (ASDEE) model is discussed.